Obtenção e caracterização de Co-amorfos do anti-hipertensivo Ramipril com o ácido oxálico - LIMA, Ylana Maria Martins (2022)
Pharmaceuticals are materials obtained with the medicinal purpose of preventing, curing diseases or alleviating their symptoms. Obtaining solid dispersions of drugs (DSFs), such as co-amorphs, has been an alternative for improving the aqueous solubility of these active principles. Ramipril (RAM) is an antihypertensive drug, it has low water solubility, which ends up reducing its bioavailability and therapeutic efficacy. This work aimed to obtain and characterize RAM co-amorphs, using Oxalic Acid (OXA) as a co-former. Molecular modeling of the starting compounds (RAM and OXA) was carried out to investigate the interaction through computational calculations developed based on the Density Functional Theory (DFT). The preparation of RAM co-amorphs was carried out using the liquid-assisted mechanochemical milling (MMLA) method. The materials were characterized by powder X- ray diffraction (XRD); Fourier transform infrared spectroscopy (FTIR); diffuse reflectance spectroscopy (DRE); thermogravimetry, derivative thermogravimetry and differential thermal analysis (TG/DTG-DTA) and differential scanning calorimetry (DSC). The physical stability of the co-amorphs was investigated by XRD as a function of time and they remained stable for at least 80 days. The results obtained by XRD showed an amorphous diffraction profile, due to the absence of crystallographic peaks. The investigation of the RAM-OXA interaction via the DFT study showed groups prone to participate in intermolecular interactions by hydrogen bonds through functional groups of nucleophilic and electrophilic character. Co- amorphs were obtained in molar ratios of 3.0:1.0; 2.5:1.0; 2.0:1.0; 1.5:1.0 and 1.0:1.0. The FTIR spectra of the co-amorphs evidenced the intermolecular interaction between the carboxyl groups of the starting compounds, confirming the results obtained via the DFT study. The ERD spectra of these co-amorphs also showed intermolecular RAM-OXA interaction. The TG/DTG curves showed that these materials showed good thermal stability at at least 170 °C. The DTA and DSC curves do not show thermal events related to melting, confirming the amorphous nature of these materials. Thus, RAM-OXA co-amorphs are promising alternatives in the treatment of arterial hypertension, based on the principle that materials with amorphous nature tend to be more water soluble than crystalline materials, favoring an increase in their bioavailability and therapeutic efficacy, as well as reducing its side effects.